Super size me - Spurlock, Morgan 1970- (Hart Sharp Video, 2004)
Morgan Spurlock wants to find out if fast food is making Americans fat, so for 30 days he eats three square meals only from McDonald's menu. He also treks across the country interviewing a host of experts on fast food and a number of regular folk while downing McDonald's to try and find out why 37% of Americans are now overweight. At the end of 30 days, the ill effects of this fastfood diet are evident on his body.